POPULATION DYNAMICS AND THE CHALLENGES OF SUSTAINABLE DEVELOPMENT - Andi Jalal Al Afgan; Supriadi Torro (PT. Jurnal Center Indonesia Publisher, 2026)
This study aims to analyze population dynamics and the challenges of sustainable development in Indonesia from a social, economic, and environmental perspective. Population dynamics, including population growth, urbanization, internal migration, and changes in demographic structure, have become determining factors in the success of development. The method used is a qualitative approach with a literature review sourced from official documents, scientific journals, and reports from international institutions. The results show that rapid population growth and uncontrolled urbanization have led to spatial inequality, reduced green open space, pressure on public infrastructure, and increased environmental degradation. Furthermore, unpreparedness in spatial planning and weak integration of population data into development policies exacerbate socio-economic imbalances between regions. The shift in demographic structure toward a predominance of the productive age group presents the opportunity for a demographic bonus, but also the risk of a demographic burden if not balanced by improvements in the quality of human resources. This study emphasizes that successful sustainable development requires data-driven, gender-equitable, environmentally friendly, and participatory population policies. The integration of technologies such as Geographic Information Systems (GIS) and spatial analysis is a strategic step in realizing inclusive, adaptive, and sustainable development for future generations.